THE THIRD RENAISSANCE IS IN THE HANDS OF DETERMINED YOUNG PEOPLE - Makhmudov Komal Samadovıch (Journals Park Publishing, 2022)
This article talks about the fact that today's modern youth is the mainstay of the "Third Renaissance", which is being laid in our country. In addition, information is provided on the conditions created in the country for the younger generation, the measures taken to implement their business plans, the ongoing reforms to ensure the employment of unemployed youth. Some shortcomings related to youth are also highlighted.
Keywords: Third Renaissance, New Uzbekistan, youth, law